The THE RELATIONSHIP OF INFORMATION GIVING PERIODICALLY WITH PSYCHOLOGICAL WELL-BEING IN PATIENTS UNDERGOING HEMODIALYSIS THERAPY (Study at Islam Jemursari Hospital Surabaya) - mufarika mufarika; Mulia Mayang Sari; Fitriah Fitriah; Nur Komariyah Mujib (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2019)
Patients have undergone hemodialysis therapy experience changes in their lifestyle such as the body's limited function, dependence on treatment, feelings of fear and worry about uncertainty about death, as well as lifestyle changes that can cause anxiety and emotional instability in patients. The purpose of this study was to determine the relation of information giving periodically with psychological well-being in patients undergoing hemodialysis therapy. This research method was analytic with cross sectional approach. Total population was 120, sample of this research was 92 respondents. Sampling was using simple random sampling, the instrument used was a questionnaire of regular information and psychological well-being questionnaires in patients undergoing hemodialysis therapy. The statistical test used Spearman Rank with significance value α 0,05. The result of the study showed that the information giving was less, that was 43 respondents (47%), while the psychological well-being was 46 respondents (50%). The result of statistical test showed that P value (0,042) <α (0,05) mean there was a relation of information giving periodically with psychological well-being in patients who undergo hemodialysis therapy at RSI Surabaya. The results of the research conducted, there was a relationship of information giving periodically with psychological well-being in patients undergoing hemodialysis therapy. It is expected that nurses can give information periodically to patients undergoing hemodialysis therapy in order to phsychological well-being of patients is high.